EFL TEACHERS’ NEED OF LANGUAGE PROFICIENCY PROFESSIONAL DEVELOPMENT: WHEN POLICY AND PRACTICE COLLIDE - Nugroho, Him'mawan Adi (International Journal of Language Education, 2018)
Align with the increasing demands of qualified and professional English as Foreign Language (EFL) teachers the need of improving the capabilities of the EFL teachers, both pre-service and in-service teachers is unavoidable. In-service EFL teachers still have to update, upgrade and refresh their competences in ELT which include their pedagogical competence (teaching skill) and professional competence (subject matter) through professional development (PD). As one of the four competencies that a teacher should have, professional competence holds an important role in helping the students to learn English well. Therefore, it is obvious that EFL teachers’ PD is essential for the teachers to support their learning leading to their empowerment as professional English teachers. This qualitative study tried to see the phenomenon of the EFL teachers’ need for language proficiency professional development by using interview as the main data collection instrument to get the information. The participants of the study were EFL teachers who joined professional teacher training program (PLPG) at Universitas Negeri Surabaya (Unesa) in 2017. The findings showed that most of the participants were very confident with their English mastery. However, they stated that they needed regular and continues PD activities specifically for their language proficiency. The activities range from maintaining the four micro skills, provide scholarship for teachers to have short course program abroad to maximizing the function of subject teacher association (MGMP).